Impulsivity as a Risk Factor for Suicide in Bipolar Disorder - Zakowicz, Przemysław; Skibińska, Maria; Wasicka-Przewoźna, Karolina; Skulimowski, Bartosz; Waśniewski, Filip; Chorzepa, Aneta; Różański, Maciej; Twarowska-Hauser, Joanna; Pawlak, Joanna (Frontiers in Psychiatry, 2021)
The accurate assessment of suicide risk in psychiatric, especially affective disorder diagnosed patients, remains a crucial clinical need. In this study, we applied temperament and character inventory (TCI), Barratt impulsiveness scale 11 (BIS-11), PEBL simple reaction time (SRT) test, continuous performance task (CPT), and Iowa gambling task (IGT) to seek for variables linked with attempted suicide in bipolar affective disorder group (n = 60; attempters n = 17). The main findings were: strong correlations between self-report tool scores and objective parameters in CPT; the difference between attempters and non-attempters was found in the number of correctly responded trials in IGT; only one parameter differed between attempters and non-attempters in BPI diagnosis; and no significant differences between suicide attempters and non-attempters in TCI, BIS-11, and SRT were found. These justify the conclusion that impulsivity itself is not a strong predictor, and used as a single variable might not be sufficient to indicate the high suicide risk group among bipolar patients.